ANALYSIS OF SIMPLE FINANCIAL BOOKKEEPERS FOR THE VEGETABLE VENDORS IN EAST BOGOR REGION - Retno Martanti Endah Lestari; Siti Maimunah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
Recently there are many vegetable vendors who have difficulties in managing their financial bookkeepers. In maintaining their capital, they borrow some money from moneylenders or mobile banks that provide higher interest than the state bank. The aim of this study is to analyze how they can maintain their financial skill. This type of research is a descriptive development survey with a qualitative research technique. Data are collected from primary and secondary data by using the questionnaires. The stratified sampling method used by taking grouping respondents get  34 people from 92 populations spread across the Bogor region. The result of this study describes there are still many vegetable vendors do not have capabilities in simple bookkeeping skills in the East Bogor Region. A lot of them do not separate the financial management of their business with their personal life. They don't take notes on the entry and expenditure because they think it's too complicated and time-consuming. Even though they have difficulties in detecting pure profits from the sales,  they still borrow some money from moneylenders to generate their capitals. They do not understand what the impact of it.